Prevalence of clinical variants of polycystic ovary syndrome - Syusyuka, V. G.; Makurina, G. I.; Sergienko, M. Yu.; Chornenka, A. S.; Yershova, O. A.; Сюсюка, Володимир Григорович; Макуріна, Галина Іванівна; Сергієнко, Марина Юріївна; Чорненька, Альона Сергіївна; Єршова, О. А. (My University, 2022)
Hyperandrogenism (HA) is the most common endocrinopathy in women, caused by excessive production of androgens by the ovaries and / or adrenal glands or increased local tissue sensitivity to circulating androgens. Frequent and characteristic manifestations of HA include dermatopathy (acne, alopecia, seborrhea, and hirsutism) and polycystic ovary syndrome (PCOS). Clinical manifestations of hyperandrogenism are acne, hirsutism (enhanced hair growth in women of the male type - in androgen-dependent areas), seborrhea, androgenetic alopecia (male pattern baldness), virilization (roughening of the voice, malnutrition of the mammary glands, android body structure). In addition, HA can be manifested by disorders of a woman's reproductive function, such as ovulation disorders, infertility and miscarriage. According to the literature, signs of HA are observed in 10-20% of women.